The Inhibitory Effect of Curcumin on Virus-Induced Cytokine Storm and Its Potential Use in the Associated Severe Pneumonia - Liu, Ziteng; Ying, Ying (Frontiers in Cell and Developmental Biology, 2020)
Coronavirus infection, including SARS-CoV, MERS-CoV, and SARS-CoV2, causes daunting diseases that can be fatal because of lung failure and systemic cytokine storm. The development of coronavirus-evoked pneumonia is associated with excessive inflammatory responses in the lung, known as "cytokine storms," which results in pulmonary edema，atelectasis and acute lung injury (ALI) or fatal acute respiratory distress syndrome (ARDS). No drugs are available to suppress overly immune response-mediated lung injury effectively. In light of the low toxicity and its antioxidant, anti-inflammatory, and antiviral activity, it is plausible to speculate that curcumin could be used as a therapeutic drug for viral pneumonia and ALI/ARDS. Therefore, in this review, we summarize the mounting evidence obtained from preclinical studies using animal models of lethal pneumonia where curcumin exerts protective effects by regulating the expression of both pro- and anti-inflammatory factors such as IL-6, IL-8, IL-10, and COX-2, promoting the apoptosis of PMN cells, and scavenging the reactive oxygen species (ROS), which exacerbates the inflammatory response. These studies provide a rationale that curcumin can be used as a therapeutic agent against pneumonia and ALI/ARDS in humans resulting from coronaviral infection.